Characteristics of excellent Islamic education lecturers in teaching education institute of Malaysia - Abdullah, Mohd. Nasri (Academic Journals, Victoria Island, Lagos, Nigeria, 2014)
This article aims to discuss the excellent attitude that is practiced by Excellent Islamic Education Lecturer (EIEL) in Teacher Education Institute of Malaysia (TEIM). This excellent attitude is identified through one of a case study that was conducted earlier. This case study is implemented in Teacher Education Institute of Malaysia, Dato' Razali Ismail Campus (TEIMDRIC) that involved comprehensive interview and observation with two EIEL and Head of Department, Department of Islamic Education and Moral Education. The result of this interview is then structured with NVivo 7.0 version to produce theme, model and matrix schedule related to the practice of excellent attitude of IEEL in Teacher Education Institute of Malaysia (TEIM). The result of the study showed that there are four aspects of excellent attitude that are practiced by EIEL during their duty in Teacher Education Institute of Malaysia. The aspects of excellent attitude are the features of outstanding attitude towards Allah, oneself, teacher trainers and colleagues.